ANALISIS WACANA FOUCAULT DALAM STUDI KOMUNIKASI - Dhona, Holy Rafika (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2019)
Michel Foucault is a popular thinker across disciplines in academia. In Indonesian communication studies, his concepts are used in several ways as an instrument analysis on many communication act/ event. The problem is only little, or even no one, wrote how to do the Foucauldian method of analysis in the context of communication studies. This article proposes how to do Foucauldian analysis in communication studies by focusing on analyzing statements, historical analysis and analysis of power. This article explains that Foucauldian discourse analysis is not textual-linguistic analysis, then it could be done in all of the research areas within communication studies, including communication researches with managerial perspectives such as public relations, business communication, advertising, and others. To cite this article (7th APA style):Dhona, H. R. (2020). Analisis Wacana Foucault dalam Studi Komunikasi [Using Foucauldian Discourse Analysis in Communication Studies]. Journal Communication Spectrum, 9(2), 189-208. http://dx.doi.org/10.36782/jcs.v9i1.2026